Relationship of Waste Management towards the Event of DHF in the Work Area of Puri Health Center, Mojokerto Regency in 2021 - Moch Yusron; Ira Nurmala; Oedojo Soedirham (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Dengue Hemorrhagic Fever (DHF) is one of the main public health problems in Indonesia. This disease is caused by the dengue virus and is transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes. DHF has spread widely throughout Indonesia, one of which is Mojokerto and its surroundings. From 2014 to 2021, the incidence rate (IR) of dengue fever in Mojokerto has increased and decreased. However, dengue cases always appear, especially in endemic areas such as Mojokerto. This study aims to analyze the relationship between waste management practices and the incidence of dengue fever in Mojokerto Regency. This research is an analytic observational study with a case control approach. The sample of the case group in this study were DHF patients at the Puri Public Health Center, Semarang Regency and the control group were healthy people or neighbors of DHF patients who lived in Mojokerto. The research sample was 27 cases and 27 controls with consecutive sampling technique. The data were processed by chi-square test. From the statistical test, it is known that there is a relationship between waste management practices (p = 0.003) and the incidence of DHF in Semarang Regency.